Ideopoliticor Education as a Means of Building Democratic Character Aisyiyah In Central Java Indonesia - Ambarsari, Arum; Pramono, Suwito Eko; Masrukhi, Masrukhi; Suyahmo, Suyahmo (Universitas Negeri Semarang, 2024)
Indonesia is a democratic country, therefore all Indonesian citizens should be able to have the character of Democracy, without exception Indonesian citizens who are female and members of the Aisyiyah organization. The purpose of this research is to describe the implementation of ideopoliticor (Ideogy, Politic, Organization) that has been carried out by Aisiyah in forming a democratic attitude to life. This research use qualitative approach, by collecting data through interview sheets and observation sheets, researchers want to find out what the implementation of ideopoliticor education has been like that has been carried out by Central Java women. Based on the research that has been carried out, data is obtained that idiopoliticor are indeed an annual work program of Aisyiyah, in its implementation presenting professional resource persons in the field of the fields of ideology, politics, and organization. All participants were very enthusiastic about participating in this event, as evidenced by the fact that some of the participants who attended were over 60 years old.